2005
DOI: 10.1128/jcm.43.12.6108-6112.2005
|View full text |Cite
|
Sign up to set email alerts
|

Rapid and Simple Method for Detecting the Toxin B Gene of Clostridium difficile in Stool Specimens by Loop-Mediated Isothermal Amplification

Abstract: We applied the loop-mediated isothermal amplification (LAMP) assay to the detection of the toxin B gene (tcdB) of Clostridium difficile for identification of toxin B (TcdB)-positive C. difficile strains and detection of tcdB in stool specimens. tcdB was detected in all toxin A (TcdA)-positive, TcdB-positive (A ؉ B ؉ ) and TcdA-negative, TcdB-positive (A ؊ B ؉ ) C. difficile strains but not from TcdA-negative, TcdB-negative strains. Of the 74 stool specimens examined, A ؉ B ؉ or A ؊ B ؉ C. difficile was recover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
33
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 29 publications
1
33
1
Order By: Relevance
“…Six false-positive results were obtained by the illumigene assay, an incidence similar to that noted by other studies (3,6). The mechanism of these false positives is unclear, although some have suggested that loop-mediated isothermal amplification is more sensitive than toxigenic culture, and these may thus represent true-positive results, albeit at very low levels of organism presence (20,21). However, others have reported that the sensitivity of the Xpert C. difficile assay, which was used as an arbiter test in our study, is greater than that of the illumigene assay (22).…”
Section: Discussionmentioning
confidence: 58%
“…Six false-positive results were obtained by the illumigene assay, an incidence similar to that noted by other studies (3,6). The mechanism of these false positives is unclear, although some have suggested that loop-mediated isothermal amplification is more sensitive than toxigenic culture, and these may thus represent true-positive results, albeit at very low levels of organism presence (20,21). However, others have reported that the sensitivity of the Xpert C. difficile assay, which was used as an arbiter test in our study, is greater than that of the illumigene assay (22).…”
Section: Discussionmentioning
confidence: 58%
“…However, the prevalence of C. difficile infection was not statistically different (P ϭ 0.12; Fisher) between PPI users (19%) and nonusers (7%). It is possible that the illumigene assay was more sensitive than TC, as suggested by others (12,19); however, this is unlikely, given the multiple and extended culture protocols used during discrepant analysis and the extended clinical follow-up on these patients. The one false-negative result with the illumigene assay was positive by GeneOhm, the GDH component of the Quik Chek Complete, and TC (discrepant analysis) and negative by both toxin assays.…”
Section: Discussionmentioning
confidence: 94%
“…The illumigene assay is based upon LAMP (12,17,18), in which primers qualitatively amplify a 204-bp region of the conserved 5= sequence of the tcdA gene within the PaLoc of toxigenic C. difficile via continuous isothermal amplification. Magnesium pyrophosphate is an amplification byproduct that forms a white precipitate that is detected via turbidimetric measurement.…”
Section: Discussionmentioning
confidence: 99%
“…The significant advantages of the LAMP method are (i) high amplification efficiency under isothermal conditions (63 to 65°C) and (ii) visual judgment based on the turbidity or fluorescence of the reaction mixture, which is kept in the reaction tube (18). Although it has thus emerged as a powerful tool to facilitate genetic testing for the rapid diagnosis of several viral and bacterial infectious diseases in clinical laboratories (5,11,13,14), the LAMP method has not been evaluated for the diagnosis of B. pertussis infection. In the present study, we developed a LAMP method for diagnosis of B. pertussis infection and evaluated its sensitivity, specificity, and applicability for clinical specimens.…”
mentioning
confidence: 99%